Disentangling different types of sexist attitudes and vote choice in Germany - Jessica Fortin-Rittberger; Christina Eder (Political Research Exchange)
With a woman as head of German government for 16 years, many hoped (or feared) for significant progress in the areas of gender equality. Rather than progress, however, contributors have noticed a rising backlash against norms of gender equality worldwide, but also in Germany. These developments have sparked a renewed interest in sexism as an explanation for (political) attitudes and behaviours. The context of the 2021 Bundestag election offers a unique opportunity to investigate the salience of these attitudes on both candidate evaluations and vote choice. We examine the interrelation of sexism, vote choice, and candidate sympathy, employing data that was collected directly before and following the German general elections, tapping into different manifestations of sexism, benevolent, modern and hostile. We find a powerful effect of sexism in more areas than previously theorized — namely negative attitudes towards women candidates and preference for populist radical right parties, but also in vote choice for conservative and liberal parties.